Relationship between Vitamin D Status and Striae Distensae: A Case-Referent Study. (9th November 2015) - Zanella, Rafaela Koehler; Valente, Denis Souto; Doncatto, Leo Francisco; Rossi, Daniele Dos Santos; Lerias, Aline Grimaldi; Padoin, Alexandre Vontobel
Abstract : Vitamin D (VD) plays a role in the skin regulation. Striae Distensae (SD) are manifestations of epidermal atrophy that occurs after tissue tearing due to overstretching or rapid growth. The objective of this study was to investigate the relation between serum VD and occurrence of SD in women who had undergone mammaplasty with silicone implants. A case-referent study was conducted. The blood values of 25-hydroxyvitamin D (25OHD) were measured before the surgery. For each patient postoperatively diagnosed with SD, four other participants submitted to the same surgery, without the development of SD, were enrolled as the healthy controls. 67 women with SD after the surgery entered the study. 268 formed the control group. In the serum of healthy controls 25OHD mean was 27 ng/mL, and SD cases presented 20 ng/mL (P = 0.01 ). Scarce values of VD have been observed in 56.71% of the cases presenting SD and in 39.91% without SD (P = 0.002 ). Chance of having VD values lower than 20 ng/mL amongst cases with SD is 2.38 (P = 0.0001 ). Lower serum levels of VD are linked to a higher occurrence of SD.